What remains behind the texts: individuals and destinies - Rohozha, Mariya; Levchuk, Larysa (Ukrainian Cultural Studies, 2022)
The idea for this conversation arose when I was commissioned to prepare a report on the development of ethical thought at the Department of Ethics, Aesthetics, and Cultural Studies of the Faculty of Philosophy at Taras Shevchenko National University of Kyiv. After studying the texts of the ethicists who taught at the university, I became interested in their images, characters, and fates-the personal dimension of what they did, the refraction of texts and fates in the life of the department with which I have been associated for a quarter of a century.
Keywords: interview